Physical activity of young patients following minimally invasive lateral unicompartmental knee replacement - Hariri, Mustafa; Hagemann, Merlin; Mick, Paul; Deisenhofer, Julian; Panzram, Benjamin; Innmann, Moritz Maximilian; Reiner, Tobias; Renkawitz, Tobias; Walker, Tilman (Journal of Clinical Medicine, 2023)
Unicompartmental knee replacement (UKR) has increased in popularity in recent years, especially in young patients with high demands on their athletic ability. To date, there are no data available on the physical activity of young patients following lateral UKR. The aim of this study was to demonstrate return-to-activity rate and sporting activity of patients aged 60 years or younger following lateral UKR with a fixed-bearing (FB) prosthesis. Thirty-seven patients aged 60 years or younger after lateral FB-UKR were included. Sporting activities were assessed using the University of California Los Angeles activity scale (UCLA) and the Tegner activity score (TAS). Clinical outcome was measured using the Oxford Knee Score (OKS), range of motion (ROM) and visual analogue scale (VAS). The mean follow-up (FU) was 3.1 ± 1.5 years and the mean age at surgery was 52.8 ± 3.1 years. The return-to-activity rate was 87.5% and 49% of patients were highly active postoperatively as defined by an UCLA score of 7 or higher. All clinical parameters increased significantly postoperatively. We demonstrated a high return-to-activity rate with nearly half of the patients achieving high activity levels. Longer FU periods are necessary to evaluate the effect of activity on implant survival.